Impact of proper surgical treatment on the survival of patients with epithelial ovary cancer - FARIA,FLAVIO HENRIQUE (2022)
ABSTRACT Objective: to evaluate the quality of surgical treatment of ovarian cancer patients and assess the impact of adequate surgical oncological treatment on disease-free survival and overall survival of patients with advanced epithelial ovarian cancer. Methods: this is an observational, retrospective study with quantitative analysis, with the collection of data in medical records of a temporal convenience sample of patients diagnosed with ovarian cancer admitted to a High Complexity Oncology Unit, in Belo Horizonte, from the period of 2014 to 2020. Results: a total of 91 patients diagnosed with ovarian cancer were evaluated, with the epithelial histopathological type being the most frequent (85%). Of this total, 68 patients (74.7%) had advanced-stage ovarian cancer. Appropriate surgical treatment was performed in 30.9% of patients with advanced epithelial ovarian cancer and the type of performed surgery was statistically significant for overall survival. This low proportion of appropriate surgical oncological treatment was not related to surgical specially or surgeon competence, but mainly to advanced disease related to patient flow at UNACON. It was not possible to confirm if the advanced-stage disease was related to tumor biology or losing time from diagnosis to oncological surgery. Conclusion: overall survival of advanced-stage epithelial ovarian cancer patients is directly influenced by appropriate surgical treatment, however, in this study, the percentage of advanced ovarian cancer receiving adequate surgical treatment was much lower than the rates reported in the literature. To improve these outcomes, we believe that surgeons should keep following patients during neoadjuvant chemotherapy to point to a better time for surgery, and clinical oncologists should better consider adequate oncological surgery as one of the pillars of ovarian cancer treatment and get more involved in facilitating surgeries.